PENERAPAN KNOWLEDGE MANAGEMENT PADA PERGURUAN TINGGI (STUDI KASUS: BAGIAN ADMINISTRASI PERGURUAN TINGGI X) - Ade Iriani; Munifah Munifah (UNIVERSITAS STEKOM, 2018)
Abstract Higher Education is an education that includes Diploma, Bachelor, Master, and other programs organized by Universities based on Indonesian culture. Administrative staff play an important role in supporting academic activities in Higher Education of course in the academic administration should have a good information system, but demkian permasalhan in academic service is still common, especially when the delivery of information that sometimes different between staff one with another. This paper intends to improve the academic service by applying Knowledge Management to the administrative staff at the university so that all parties can perform their obligations in accordance with their respective obligations and get their rights as appropriate.